PENGARUH BRAND IMAGE, BRAND AWARENESS, DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK CIPTADENT DI KOTA BATAM - Kenzy Tan; Yvonne Wangdra (SCIENTIA JOURNAL, 2025)
In everyday life, people are expected to pay attention to their health and appearance, especially their dental and oral health. This study aims to determine the influence of brand image, brand awareness, and perceived quality on purchase decision for Ciptadent products in Batam City. Using quantitative methods, this study sampled 385 respondents with purposive sampling, with the criteria of people who have purchased Ciptadent products. The data collection was carried out by distributing questionnaires accessed through Google Forms. Data analysis includes validity test, reliability test, classical assumption test including normality tests, multicollinearity test and heteroscedasticity test, as well as multiple linear regression test, determinant coefficient analysis, t-test, and F-test. The results of the study indicate that each variable, such as brand image, brand awareness, and perceived quality, has a partial effect on purchase decision, and they also simultaneously influence purchase decision.